A meta-analysis to explore the role of design thinking in enhancing creativity as learning outcomes in STEM education - Sumaiya Muneer (22827419) (2025)
This paper systematically reviews informal Design Thinking (DT) models in Science, Technology, Engineering, and Mathematics STEM education and performs a meta-analysis to assess their impact on students' creativity. Following Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) guidelines, data sources include eighteen peer-reviewed research papers from 11 countries, representing more than 1,600 students. The meta-analysis, using a random-effects model, assessed the effect size (ES) of informal DT in enhancing creativity in STEM education and revealed a significant improvement compared to traditional classroom education (d = 0.876, p< 0.001). This study found that several moderator variables influenced the impact of informal DT on students’ creativity, including teaching methodology, assessment methods, subject area, student group size, course duration, and grade level. Moderator analysis revealed that the combination of direct and indirect assessment (d = 1.163, p = 0.010) and triangulation assessment methods (d = 1.009, p < 0.001) had the highest effect size and significance. Student study sizes of 30 or more (d = 1.143, p < 0.001) were most effective, and informal DT employed for the subject areas like STEM (d = 1.165, p < 0.001) and science/math (d = 0.988, p < 0.001) exhibited the greatest creativity improvements. However, the study location of the students was not a significant moderator. This study provides valuable insights into existing literature. It aids academicians in designing, developing, and implementing successful STEM-based informal DT models in STEM education, and aids educators in developing innovative approaches to enhance creativity. Other Information Published in: International Journal of Technology and Design Education License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1007/s10798-025-10005-2